Pengembangan Bahan Ajar Strukturalisme Genetik untuk Pengkajian Prosa di Perguruan Tinggi (Tinjauan pada Karya Okky Madasari) - M. Ghufroni An’ars; M. Yanuardi Zain (Ksatra: Jurnal Kajian Bahasa dan Sastra, 2022)
The theory of genetic structuralism appears as a theory with a broad scope because it considers aspects outside the text. This breadth of coverage is often considered a problem in studying genetic structuralism, especially in the practice of studying prose in universities. However, the theory of genetic structuralism can be operated more simply, while still taking into account the limitations given by Goldmann. It was this simplification idea that prompted the preparation of the teaching material "Understanding Genetic Structuralism: An Overview of Okky Madasari's Short Stories" as a guide that students can use in studying the theory of genetic structuralism more practically. In carrying out this research, Borg & Gall's Research & Development method was applied by taking into account the theoretical principles of genetic structuralism as the main content in the prepared teaching materials. This research was conducted in 10 stages as follows: (1) analysis of potential problems; (2) preliminary study; (3) data collection in the form of higher education curriculum analysis and literature study; (4) preparation of teaching materials; (5) design of teaching materials; (6) validation of teaching materials; (7) testing of teaching materials in the form of small and large scale trials; (8) final product; (9) calculation of the feasibility of teaching materials in its application in tertiary institutions. The result achieved based on this research is the compilation of genetic structuralism teaching materials for the study of prose in universities. The attractiveness aspect of the two product test locations got an average score of 89,05, the ease of use aspect got an average score of 89.15, and the usability aspect got an average score of 89,04, so the overall average score was 89,01. Based on this percentage, it can be concluded that the genetic structuralism teaching materials designed have been appropriate to be applied in the study of literature in universities.